Ultrasensitive method to quantify intracellular zidovudine mono‐, di‐ and triphosphate concentrations in peripheral blood mononuclear cells by liquid chromatography–tandem mass spectrometry. (4th June 2015) - Kinai, Ei; Gatanaga, Hiroyuki; Kikuchi, Yoshimi; Oka, Shinichi; Kato, Shingo
<x xml:space="preserve">Abstract</x> In years since AZT was first used to treat HIV‐infected patients other retroviral drugs have replaced AZT for treating adult patients but it continues to be used for treating at‐risk infants and HIV‐infected children despite concerns about toxicity. Producing pharmacokinetic information from infants has been limited by limited blood sampling and imprecise and complex quantitative assays. In the Special Feature, Kinai and co‐workers at the National Center for Global Health, Tokyo, and Medicine and Keio University School of Medicine, Tokyo, present a new LC‐MS/MS method for quantifying AZT‐mono, ‐di and ‐tri phosphate in blood mononuclear cells